Neural and Behavioral Correlates of Attentional Inhibition Training and Perceptual Discrimination Training in a Visual Flanker Task - Melara, Robert D.; Singh, Shalini; Hien, Denise A. (Frontiers in Human Neuroscience, 2018)
ABSTRACT Two groups of healthy young adults were exposed to three weeks of cognitive training in a modified version of the visual flanker task, one group trained to discriminate the target (discrimination training) and the other group to ignore the flankers (inhibition training). Inhibition training, but not discrimination training, led to significant reductions in both Garner interference, indicating improved selective attention, and in Stroop interference, indicating more efficient resolution of stimulus conflict. The behavioral gains from training were greatest in participants who showed the poorest selective attention at pretest. Electrophysiological recordings revealed that inhibition training increased the magnitude of Rejection Positivity (RP) to incongruent distractors, an ERP component associated with inhibitory control. Source modeling of RP uncovered a dipole in the medial frontal gyrus for those participants receiving inhibition training, but in the cingulate gyrus for those participants receiving discrimination training. Results suggest that inhibitory control is plastic; inhibition training improves conflict resolution, particularly in individuals with poor attention skills.